Bladder Cancer Sample Handling and Reporting: Pathologist's Point of View - Mazzucchelli, Roberta; Marzioni, Daniela; Tossetta, Giovanni; Pepi, Laura; Montironi, Rodolfo (Frontiers in Surgery, 2021)
The aim of this narrative review is to provide adequate information on handling and reporting of the bladder cancer samples to improve the closely collaboration between pathologists and urologists. The main (but not exclusive) research tool used was PubMed and 87 references were selected and quoted in the text. We have considered handling of biopsies, transurethral resection (TUR), and cystectomy specimens to summarize the different methods of sampling and the related issues. Moreover, we considered and discussed the main prognostic factors, such as histological tumor type, grade, and stage of bladder cancer, that should be described in the pathological report. In addition, critical issues encountered in the interpretation of histological samples were discussed.